Barriers and Facilitators to Implementing Point‐of‐Care Ultrasound to Confirm Gastric Tube Placement in Preterm Infants: A Qualitative Study. - Wang, Yajing; Zhou, Jiong; Zhang, Jiahua; Li, Yunwei; Jing, Yalin; Xie, Yuting; Chen, Yao; Zhou, Ying; Jiang, Jingjing; Feng, Shuju; Fontenot, Justin (Journal of Nursing Management, 2026)
Aim: To explore the barriers and facilitators influencing the use of point‐of‐care ultrasound (POCUS) for confirming the position of gastric tubes in preterm infants in the neonatal intensive care unit (NICU). Background: Many research studies indicated that POCUS is an effective and repeatable technique for monitoring the tip position of gastric tubes; however, the application rate of this technique among nurses in the NICU for confirming the position of gastric tubes in preterm infants remains low. Methods: Using a qualitative descriptive research design, we conducted interviews with direct care nurses (n = 8), frontline doctors (n = 2), and nursing leaders (n = 2) at a tertiary‐level hospital to explore the barriers and facilitators influencing nurses' use of POCUS for confirming the position of gastric tubes in preterm infants. Results: The study identified two main themes: facilitators and barriers. The facilitators include the following six subthemes: adequate resource allocation and equipment; demonstrable safety and clinical efficacy; intrinsic motivation and professional development; supportive and innovative work environment; strong managerial and leadership support; and clear pathways for process optimization. The barriers also include six subthemes: deficiencies in competency development systems; complexity of neonatal clinical presentations; absence of institutional policies and standardized protocols; sociocultural and cognitive resistance; perceived legal and ethical risks; and unclear team collaboration dynamics. Conclusion: This study explored the main factors hindering and promoting the implementation of the POCUS for gastric tube position confirmation from the perspectives of direct care nurses, frontline doctors, and nursing leaders. Participants pointed out that there were issues with insufficient protection and support in areas such as training systems, institutional regulations, cognitive levels, and team collaboration. Therefore, it is necessary to formulate strategies and policies to address these obstacles.